Differential modulation of cell morphology, migration, and Neuropilin-1 expression in cancer and non-cancer cell lines by substrate stiffness - Vela-Alcántara, Ana Monserrat; Santiago-García, Juan; Barragán-Palacios, Madeleine; León-Chacón, Aylin; Domínguez-Pantoja, Marilú; Barceinas-Dávila, Irene; Juárez-Aguilar, Enrique; Tamariz, Elisa (Frontiers in Cell and Developmental Biology, 2024)
Physical changes in the tumor microenvironment, such as increased stiffness, regulate cancer hallmarks and play an essential role in gene expression, cell morphology, migration, and malignancy. However, the response of cancer cells to stiffness is not homogeneous and varies depending on the cell type and its mechanosensitivity. In this study, we investigated the differential responses of cervical (HeLa) and prostate (PC-3) cancer cell lines, as well as non-tumoral cell lines (HEK293 and HPrEC), to stiffness using polyacrylamide hydrogels mimicking normal and tumoral tissues. We analyzed cell morphology, migration, and the expression of neuropilin 1 (NRP1), a receptor involved in angiogenesis, cell migration, and extracellular matrix remodeling, known to be associated with cancer progression and poor prognosis. Our findings reveal that NRP1 expression increases on substrates mimicking the high stiffness characteristic of tumoral tissue in the non-tumoral cell lines HPrEC and HEK293. Conversely, in tumoral PC-3 cells, stiffness resembling normal prostate tissue induces an earlier and more sustained expression of NRP1. Furthermore, we observed that stiffness influences cell spreading, pseudopodia formation, and the mode of cell protrusion during migration. Soft substrates predominantly trigger bleb cell protrusion, while pseudopodia protrusions increase on substrates mimicking normal and tumor-like stiffnesses in HPrEC cells compared to PC-3 cells. Stiffer substrates also enhance the percentage of migratory cells, as well as their velocity and total displacement, in both non-tumoral and tumoral prostate cells. However, they only improve the persistence of migration in tumoral PC-3 cells. Moreover, we found that NRP1 co-localizes with actin, and its suppression impairs tumoral PC-3 spreading while decreasing pseudopodia protrusion mode. Our results suggest that the modulation of NRP1 expression by the stiffness can be a feedback loop to promote malignancy in non-tumoral and cancer cells, contingent upon the mechanosensitivity of the cells.